Evaluating LNG-Diesel Dual-Fuel Systems in Trawling: Results from Trials off Cochin, Kerala: Evaluating Dual-Fuel Systems in Trawling - Baiju, Malikayil Vijayan; V. R. Madhu; Dhiju Das, P. H.; Vipin Kumar V.; Sajeev Nambiar; Nilender Kumar; Upinder Kumar; Veerasamy Manimaran (Fishery Technology, 2024)
The trawling sector, though contributes significantly to the Indian marine fisheries, is characterized by high energy consumption and significant environmental impacts. This study investigates the feasibility and effectiveness of using a dual fuel system, combining traditional High-Speed Diesel (HSD) with Liquefied Natural Gas (LNG) in trawling operations along the Kerala coast. The field trials, conducted over four months, demonstrated that the LNG substitution rate could reach up to 24%, resulting in reductions in fuel costs and emissions. The fuel consumption pattern showed an average HSD consumption of 25.5±1.12 litres per hour during steaming and 20.4±0.74 litres per hour during trawling operations. LNG contributed to reducing HSD use by 21.0±0.56% during steaming and 29.6±0.69% during trawling. The dual-fuel system showed no significant differences in power output. The environmental impact assessment using Life Cycle Assessment (LCA) methodologies indicated significant reductions in global warming potential (19.42%), acidification potential (24.20%), and other environmental parameters when using the dual-fuel system compared to HSD alone. The study concludes that LNG can be effectively used in a diesel dual-fuel mode for trawling without any significant reduction in power or other operational parameters. Within the tested limits, it offers both economic and environmental benefits. However, the long-term viability of LNG as a sustainable  fuel source requires further research, particularly concerning infrastructure costs and lifecycle environmental impacts.